Dakwah di Era Digital: Konsep Dakwah Pegeant pada Komunitas Duta Wisata Raka Raki Jawa Timur - Nurfaiza, Ulfi (Academic Journal of Da'wa and Communication, 2025)
In the digital era, the world of da'wah (Islamic outreach) has developed rapidly, one of which is through interest-based communities. Anyone can now da'wah with the intention of spreading goodness, such as the Raka Raki Tourism Ambassador Community in East Java. This community plays a role in da'wah through tourism promotion, public education, and inspiring the younger generation to preserve culture and appreciate East Java's tourism potential. The ambassadors not only promote destinations but also convey moral messages aligned with Islamic values through digital platforms. The aim was to examine the da'wah pageant in the digital era carried out by the Raka Raki Tourism Ambassador Community in East Java. This study used a qualitative method with a phenomenological approach, through in-depth interviews, observation, and documentation. The findings show that the Tourism Ambassadors internalize their role by developing a positive self-identity, collaborating with the community, and creatively utilizing digital media to spread positive and educational messages. Their efforts demonstrate the fusion of cultural promotion and Islamic da'wah in the contemporary digital space.